THE IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS FOR ENTITIES WITHOUT PUBLIC ACCOUNTABILITY (SAK ETAP) IN SMALL AND MEDIUM ENTERPRISES (SMEs) LAWAR PONTIANAK - B41111137, Fajar Rizqi Afdau (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
Research aimed at UKM Lawar Pontianak shop that do not have the financial statements based SAK ETAP. The purpose of this study was to determine the application and the constraints faced in preparing the financial statements of Financial Accounting Standards for Entities Without Public Accountability (SAK-ETAP) in UKM Lawar Pontianak. This study used a qualitative descriptive method of data collection techniques are interviews, documentary studies, and research literature.. This study used two analytical tools, SAK ETAP and interview questions. Technical analysis in this study is the financial report made by the financial statements that the UKM Lawar Pontianak to know how the application of financial reporting standards for UKM has been carried out or not, comparing the elements of financial statements in accordance with SAK ETAP and analyze the constraints faced in the implementation of SAK ETAP in Lawar Pontianak , Results from this study is Lawar Pontianak yet to implement the preparation of financial statements in accordance with SAK ETAP. Constraints faced that Pontianak Lawar yet to implement financial statements using SAK ETAP due to lack of understanding and knowledge of the preparation of financial statements in accordance with SAK ETAP and the lack of supervision of the relevant government authorities on the financial statements.Keywords: financial statements, SAK ETAP, UKM